Pengembangan Media Biosong untuk Meningkatkan Pemahaman Peserta Didik Kelas X SMA pada Materi Sistem Klasifikasi Tumbuhan - Husmayani Muny Putri; Upik Yelianti*; Mia Aina (Jurnal Pendidikan Sains Indonesia, 2022)
The weak ability of students to understand the material of the plant classification system is due to the large amount of material and scientific names that are not even known by students. The use of media that is still less varied and interesting causes boredom because there are too many writings and few pictures. During learning, students often listen to songs in secret to eliminate boredom. Therefore, media that is suitable to the needs and interests of students is needed, namely the biosong media (biology song). The purpose of this study was to develop biosong media on plant classification system materials. This study uses the ADDIE development model which consists of the Analysis, Design, Development, Implementation Evaluation stages. Sampling was done by non-probability sampling using purposive sampling technique. Data collection was carried out through the validation of material experts, media experts, student trials and teacher responses using questionnaires. The results of material expert validation are 78.1% and media experts are 99% with very good categories with the conclusion that the media is feasible and can be tested on students. The results of the small group trial at the implementation stage were 77.6% and the large group was 88.5% with a very good category. The result of the teacher's assessment of biology subjects was 90.6% with a very good category. Thus, it can be concluded that the developed biosong learning media is feasible to be used as a learning medium and can help students learn the plant classification system material